Covenant and creation an Old Testament covenant theology - Dumbrell, William J. 1926-2016 (Milton Keynes, England Paternoster, 2013)
Contents -- ABBREVIATIONS -- PREFACE -- THE COVENANT WITH CREATION -- THE COVENANT WITH ABRAHAM -- THE SINAI AND MOSAIC COVENANTS -- THE DAVIDIC COVENANT: THE COVENANT AND MESSIAHSHIP -- THE NEW COVENANT -- THE POST-EXILIC DEVELOPMENTS -- BIBLIOGRAPHY -- Endnotes
Includes bibliographical references. - Online resource; title from PDF title page (ebrary, viewed August 29, 2014)
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Covenants; Bible; Bible; Bible -- Criticism, interpretation, etc; Bible -- Covenants; Bible. -- Old Testament -- Covenants; Bible. -- Old Testament -- Criticism, interpretation, etc; Covenant Theology -- Biblical teaching; Covenant Theology -- Biblical teaching; RELIGION ; Christian Theology ; General; Covenants; Criticism, interpretation, etc; Electronic books -- Criticism, interpretation, etc